1995
DOI: 10.1002/hlca.19950780524
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis with a Chirogenic Opening Move Demonstrated on Steroids with Estrane or 18a‐Homoestrane Skeleton

Abstract: Dedicated to Albert Eschenmoser on the occasion of his 70th birthday (12.VI.95)A concept of first choice for the synthesis of the title compounds had been proposed by Dane in the late 1930s. It was soon turned down, because the opening move -a chirogenic Diels-Alder reaction -did not work. With Lewis acids as mediators, however, a successful start has been achieved now. With Ti complexes of chelating ligands (Seebach 's TADDOLs ( = a,a,a',a'-tetraaryl-1,3-dioxolane-4,5-dimethanols)), enantioselective formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 85 publications
1
38
0
Order By: Relevance
“…This type of acid-induced isomerization is well precedented in earlier Dane's-diene-based routes to steroids (39)(40)(41)(42)(43). It should be noted that when conducted thermally, DA reactions of cyclenones with 26 are not significantly regioselective (44,45). Thus, one would have expected, by precedent, that the thermally driven DA reaction of 7 with Dane's diene would have also produced 29 as a seriously competing primary product.…”
Section: Significancementioning
confidence: 70%
“…This type of acid-induced isomerization is well precedented in earlier Dane's-diene-based routes to steroids (39)(40)(41)(42)(43). It should be noted that when conducted thermally, DA reactions of cyclenones with 26 are not significantly regioselective (44,45). Thus, one would have expected, by precedent, that the thermally driven DA reaction of 7 with Dane's diene would have also produced 29 as a seriously competing primary product.…”
Section: Significancementioning
confidence: 70%
“…Since the trifluoromethanesulfonyl group is highly electron-withdrawing in nature, the electrophilic reactivity of the ketone is significantly high in converting to a dioxilane, and the electronwithdrawing character of the amide retards Baeyer-Villiger oxidative rearrangement. These strongly indicated that electrophilic activation of ketone is possible by attaching electron-withdrawing sulfonylamide groups on both a-methylene carbons of the ketone, but not by bulky sulfonylamide (2, 3, 7) and ether group (8).…”
mentioning
confidence: 97%
“…According to the reported procedure, 9 was arylsulfonated with the corresponding chlorides in methylene chloride giving 10a, b. 8) Cyclization of 10 was carried out with to afford olefins 11a, b, which were then ozonolyzed to the ketones 2 and 3 (Chart 1).…”
mentioning
confidence: 99%
“…Prominent among the methods that have been developed are those based on Diels-Alder reactions (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), transition metal-catalyzed cyclizations of enynes and triynes (13)(14)(15)(16), and biogenetic-type electrophilic cyclizations of polyene precursors (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%